2014
DOI: 10.1021/es405449v
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism for the Aqueous-Phase Mineral Carbonation of Heat-Activated Serpentine at Low Temperatures and Pressures in Flue Gas Conditions

Abstract: Mineral carbonation is known as one of the safest ways to sequester CO2. Nevertheless, the slow kinetics and low carbonation rates constitute a major barrier for any possible industrial application. To date, no studies have focused on reacting serpentinite with a relatively low partial pressure of CO2 (pCO2) close to flue gas conditions. In this work, finely ground and heat-treated serpentinite [Mg3Si2O5(OH)4] extracted from mining residues was reacted with a 18.2 vol % CO2 gas stream at moderate global pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 46 publications
2
40
0
Order By: Relevance
“…Similar work conducted in laboratory scale led to a reaction efficiency of 0.28 g of CO 2 converted.g of serpentine -1 (Pasquier et al, 2014b). The difference between the results can be attributed to several factors.…”
Section: Effect Of Heat-treatment Of Mineral Carbonation Residuementioning
confidence: 65%
See 1 more Smart Citation
“…Similar work conducted in laboratory scale led to a reaction efficiency of 0.28 g of CO 2 converted.g of serpentine -1 (Pasquier et al, 2014b). The difference between the results can be attributed to several factors.…”
Section: Effect Of Heat-treatment Of Mineral Carbonation Residuementioning
confidence: 65%
“…In this way, different studies focused on using a diluted CO 2 stream, similar at some industrial flue gas (Pasquier et al, 2014a;Werner et al, 2014). Results showed that reaction mechanism, kinetics where similar as observed for pure CO 2 treatments and led to promising results Pasquier et al, 2014b). In addition, dissociation of gas treatment steps and carbonates precipitation leads to the production of high purity products giving significant incomes.…”
Section: Introductionmentioning
confidence: 93%
“…Recent research has shown that it is feasible to use heat treated serpentine to treat directly the flue gas from a cement plant containing 18% CO 2 instead of pure CO 2 . This research shows that it is possible to produce pure Nesquehonite by precipitating in a separate step.…”
Section: Introductionmentioning
confidence: 92%
“…[53][54][55][56][57] Direct carbonation involving serpentinite and forsterite rocks has been proposed. [58][59][60][61] In this case, the CO 2 is dissolved in solution forming carbonic acid. This causes a pH reduction in the medium, allowing the dissolution of the magnesium silicate and the subsequent carbonation.…”
Section: Absorption/capture Of Comentioning
confidence: 99%